2022
DOI: 10.1155/2022/5112375
|View full text |Cite|
|
Sign up to set email alerts
|

A Neighborhood and Machine Learning-Enabled Information Fusion Approach for the WSNs and Internet of Medical Things

Abstract: Data redundancy or fusion is one of the common issues associated with the resource-constrained networks such as Wireless Sensor Networks (WSNs) and Internet of Things (IoTs). To resolve this issue, numerous data aggregation or fusion schemes have been presented in the literature. Generally, it is used to decrease the size of the collected data and, thus, improve the performance of the underlined IoTs in terms of congestion control, data accuracy, and lifetime. However, these approaches do not consider neighbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The simplest and easiest methods are often used by attackers to gain access to a network or device. The device becomes the first point of entry for an attacker if it is vulnerable to spiteful scripts and misdirection caused by inadequate code testing [75,76]. Based on three layers of IoT architecture, Figure 9 illustrates the most common threats.…”
Section: Resultsmentioning
confidence: 99%
“…The simplest and easiest methods are often used by attackers to gain access to a network or device. The device becomes the first point of entry for an attacker if it is vulnerable to spiteful scripts and misdirection caused by inadequate code testing [75,76]. Based on three layers of IoT architecture, Figure 9 illustrates the most common threats.…”
Section: Resultsmentioning
confidence: 99%
“…However, data latency and privacy are some major research objectives in the cloud-based paradigm. Many machine learning-based methods have been proposed to solve the process of data aggregation and routing issues for IoT-based constraint networks and drastically reduce the disturbance of wireless channels [9][10][11]. However, the collaboration of heterogeneous IoE demands for edge computing to bring the data processing closer towards the source network.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%